On the equiconvergence of the spectral decomposition of the distributions connected with elliptic differential operators on the torus with fourier integral - Akhmedov, Abdulkasim; Salleh, Zuki; Rakhimov, Abdumalik (Institute of Physics Publishing, 2021)
The problems of engineering sciences can be modelled using equations of mathematical physics. Mathematical models for many systems that are encountered in engineering, physics, and other applied sciences are often developed by applying various laws that describe the conservation of mass, momentum, and energy. These models are usually given as a single or set of ordinary or partial differential equations along with appropriate initial and boundary conditions which apply over the rectangular region. Solution of these equations using appropriate analytical methods provides local numerical values for the dependent variables of interest, such as fluid velocity, pressure, species concentration, temperature, force and electric potential.